ON ONE ALGORITHM OF APPROXIMATE CONTROL OF FLEXIBLESYSTEMS - Ghukasian, A. A.; Hayrapetian, V. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
On the basis of mathematical models control algorithms are investigated for two elastic mechanical systems (flying object, elastic manipulator). Control parameters are found that provide damping of the first mode of elastic oscillations at the end of movement. The oscillation graphics of the elastic element of those systems are presented for the found control algorithms.
Keywords: control algorithms; flying object; elastic manipulator